Studi Analisa Kerusakan Jalan Menggunakan Metode Bina Marga dan Pavement Conditian Index (Studi Kasus : Ruas Jalan Napal Peranap) - Susono Susono; Arif Sudaryanto; Erny Erny (Jurnal Sipil Terapan, 2023)
Assessment of road surface conditions is a form of road maintenance and repair efforts. The two methods used in assessing road conditions are the Bina Marga method and the PCI (Pavement Condition Index) method. This study aims to compare the condition values ​​of the Peranap Napal road sections based on the two methods. The types of damage that can be found on the Napal Peranap road section are 7 types of damage consisting of: crocodile skin cracks (1.66%), elongated cracks (0.16%), edge cracks (0.08%), road joint cracks (0.01%), fillings (0.74%), holes (0.02%) and grain discharge (3.62%) with a total damage area of ​​2644.02 m2 or (6.30%) of 42000 m2 the area of ​​the Peranap Napal road studied. The Bina Marga method obtained a Priority Order (UP) value of 4 (included in the periodic maintenance program), while the PCI method obtained a damage level value of 66.16 (in fair condition with yellow color). The results of these two methods turned out to produce relatively the same assessment, namely the condition of the road section still required maintenance and repair, including: providing additional layers, making and repairing drainage, widening and compacting the shoulders, filling gaps with a mixture of asphalt and sand, and dismantling the pavement layer. and then re-coated with the same material.